Ammi majus Seed Extract Cardioprotective Effect Against Doxorubicin Cardiotoxicity in Mice - Jasim , Israa AJ; Mutlag, Shihab H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
One of the most efficient anthracycline anti-cancer medications, doxorubicin, is used to treat lymphoid malignancies. Intercalation with deoxyribonucleic acid is a key component of its primary chemotherapeutic mode of action, which can ultimately lead to heart failure. Therefore, the objective of this study was to determine whether the ethanolic extract of Ammi majus had any cardioprotective effects against doxorubicin toxicity in mice. 48 mature Albino male mice were separated into six groups and distributed as follows: for 14 days, Group I: "negative control" received distilled water; Group II: mice received a single oral daily dose of 64 mg/kg of Ammi majus seeds extract; Group III: mice received a single oral daily dose of 128 mg/kg of Ammi majus seeds extract; and Group IV: "positive control" received a single dose of 2 ml/kg of distilled water. On day fifteen, the mice got an intraperitoneal dose of 15 mg/kg of Doxorubicin; they were sacrificed using anesthetic ether 24 hours later. Group V was given a single dose of 15 mg/kg of doxorubicin on day 15 after receiving 64 mg/kg/day of Ammi majus. Finally, group VI mice received 128 mg/kg of Ammi majus, and on day 15, they got a single dosage of 15 mg/kg of doxorubicin. To analyze malondialdehyde, creatine kinase-myoglobin binding, and creatine phosphokinase as indicators of cardiotoxicity, the blood was drawn from the preorbital sac. Data analysis revealed that mice pre-treated with different doses of Ammi majus extract (64 mg and 128 mg/kg) significantly reduced the heart damage as compared to animals intoxicated by Doxorubicin, as evidenced by an increase in malondialdehyde, creatine kinase-myoglobin, and creatine phosphokinase in the Doxorubicin group. So the alcoholic extract of Ammi majus seeds reduced the heart injury in pretreated mice, because of its active constituent, which has anti-inflammatory action and antioxidant properties.